(untitled) - Department of Foreign Affairs and Trade (Carlton, Vic., 2000)
The book provides full documentary coverage of period of transfer from one power to another, beginning with the advent in April 1974 of a new government in Lisbon, presaging the dissolution of Portugal's overseas empire, and eding with president Soeharto's siging of the bill incorporating East Timor as the twenty-seventh province of Indonesia,....
Keywords: Đông Timo; Chính phủ và chính trị